Income Inequality of the Brazilian Amazon Population - Braga de Almeida-Gabriel , Flávio; Ribeiro, Márcio Luiz; Felipe Ferreira da Luz , João; Augusto Lira Vaz da Costa, Carlos (Revista Brasileira de Estudos Regionais e Urbanos, 2023)
The main objective of this study is to evaluate the behavior of income distribution in the Amazo-nian States of Brazil from 2004 to 2015. As complementary objectives, we sought to determine theimmediate causes of any differences of Household IncomePer Capita(HIPC) distribution in theLegal Amazon, based on the static decomposition of the Gini Index, and to analyze the dynamicdecomposition of the Gini Index considering HIPC portions. This methodology used microdatafrom the National Household Sample Survey (PNAD) for the analyzed period. As a result, the Giniindex of the Legal Amazon HIPC performed differently from that of Brazil (without Legal Amazon).The HIPC portion formed by the income of military and civil servants from the Legal Amazonstood out for having the highest degree of negative progressivity when compared to the rest of thecountry, whereas “government transfers” had the highest degree of positive progressivity, beingresponsible for 36.7 of the Gini Index variation from 2004 to 2015.